DETERMINATION OF RATIONAL PARAMETERS OF THE LEVER - Haydarov Sh. B.; Usmonov M. Z.; Saidova L. F. (Web of Journals Publishing, 2024)
This article examines the influence of adverse investigative factors resulting from the recoil forces of the excavator and bucket, as well as the trajectory of the bucket in the working area. The lever must be made of durable material, taking into account the tension forces on the gear and the identification of many malfunctions of the lever.